Workers' compensation injury claims among workers in the private ambulance services industry—Ohio, 2001–2011. Issue 12 (12th November 2018) - Reichard, Audrey A.; Al‐Tarawneh, Ibraheem S.; Konda, Srinivas; Wei, Chia; Wurzelbacher, Steven J.; Meyers, Alysha R.; Bertke, Stephen J.; Bushnell, P. Timothy; Tseng, Chih‐Yu; Lampl, Michael P.; Robins, David C.
Abstract : Background: Ambulance service workers frequently transfer and transport patients. These tasks involve occupational injury risks such as heavy lifting, awkward postures, and frequent motor vehicle travel. Methods: We examined Ohio workers' compensation injury claims among state‐insured ambulance service workers working for private employers from 2001 to 2011. Injury claim counts and rates are presented by claim types, diagnoses, and injury events; only counts are available by worker characteristics. Results: We analyzed a total of 5882 claims. The majority were medical‐only (<8 days away from work). The overall injury claim rate for medical‐only and lost‐time cases was 12.1 per 100 full‐time equivalents. Sprains and strains accounted for 60% of all injury claims. Overexertion from patient handling was the leading injury event, followed by motor vehicle roadway incidents. Conclusions: Study results can guide the development or improvement of injury prevention strategies. Focused efforts related to patient handling and vehicle incidents are needed.